A comparison of the Ponzo illusion with a textural analogue - Fineman, Mark B; Carlson, Jeffrey (Attention Perception & Psychophysics, 1973)
The inappropriate constancy scaling notion of geometric illusions was explored by employing a textural analogue of the Ponzo figure. Ten Ss estimated the length of a horizontal line by equating it with varying companion lines in the context of the Ponzo figure, a textural analogue, and a baseline control in which the lines appeared with no surrounding contours. The textural analogue had the added feature of imposing no contours at the ends of the horizontal lines. It was found that length estimates were significantly different between the horizontals of the Ponzo figure and control stimuli, but not between the texture figure and a context-free control. The results suggest that inappropriate constancy scaling plays a minor role at best in the perception of geometric illusions. © 1973 Psychonomic Society, Inc.
Keywords: dept.psy; normal human; theoretical study; visual illusion

Consequences of transgression: self-punishment and depression. - Wallington, Sue A (Journal of Personality and Social Psychology, 1973)
Assessed the effects of transgression on self-aggression and depression in 96 high school students. Male confederates induced 1/2 of the Ss to transgress by deceiving the E. As a measure of self-aggression all Ss gave themselves electric shocks of intensity which they personally selected. Ss were also given behavioral and subjective-report measures of depression, including the Mood Adjective Check List. Transgressing Ss showed significantly more self-aggression. Transgressing Ss also showed changes on behavioral measures of depression but not on subjective-report measures. Females showed significantly more self-aggression than males regardless of condition. Findings suggest that the altruistic behavior found to occur after transgression may be engaged in for its self-punitive aspect as well as, or rather than as, a means of social restitution, as has been previously suggested. Contrary to the suggestion of some theories of depression, self-punishment did not appear to alleviate depression. (21 ref) (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1973 American Psychological Association.
Keywords: Aggression; Depression; Electroshock; Female; Guilt; Human; Male; Morals; Orientation; Personality Inventory; Psychological Theory; Punishment; Self Concept; Sex Factors; Social Behavior; aggression; article; depression; depression, high school students; dept.psy; electric shock; female; guilt; human; male; morality; orientation; personality test; psychological theory; punishment; self concept; sex difference; social behavior; transgression, self-aggression &